The Recognition and Reward of Employee Performance - Bishop, John (Journal of Labor Economics, 1987)
This paper examines when and to what extent an individual's relative wage depends on his/her productivity relative to others doing the same job. Starting wages were influenced by background characteristics and training cost realizations but not by relative productivity. Wages one year later were influenced by productivity but the effects were small. The wage elasticity was .2 at small establishments and 0 at establishments with over 400 employees. The wage response to relative productivity and training costs was weaker in small labor markets, suggesting that wages do not fully respond to performance because of the firm specificity of job performance differentials.